PENERAPAN METODE WATERFALL DAN FRAMEWORK CODEIGNITER DALAM PERANCARANGAN SISTEM E-COMMERCE BERBASIS WEBSITE PADA TOKO EDO GORDEN (E-GO) - Rousyati Rousyati; Fandhilah Fandhilah; Fatimah Fatimah; Ira Puspitasari; Ahmad Syamsul Falah (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2022)
Technology has become a necessity for many people even in carrying out daily activities. Technology is used in various ways such as sales promotion, data management or in conducting transactions. Based on observations that have been made, there are still many shops in the Tegal area, especially curtain shops that still use the manual sales system. One of them is at the Edo Gorden Store which is an MSME in Tegal City which still sells manually so it is not well organized from recording sales reports, sales systems and transactions that still use conventional. This supports customers in transactions and could be one of the causes of decreased customer interest. The design of a web-based sales application is a solution to this problem that can help expand the marketing and business promotion area with the support of the internet. The website design uses the Unified Modeling Language modeling which is built with the CodeIgniter Framework and the PHP programming language. Web-Based Curtain sales information system at UD. The Neat Gorden Jombang that has been done can manage data orders, payments and customer testimonials more efficiently.